Penerapan Teknik Chunking untuk Mengendalikan Beban Kognitif Intrinsik Siswa SMA Pada Pembelajaran Sistem Reproduksi Manusia - Meirin Dwiningtyas Putri; Adi Rahmat; Yayan Sanjaya (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2021)
Intrinsic cognitive load is related with the load of processing information received. This study aims to control the intrinsic cognitive load students by applying chunking technique of the human reproductive system learning. The research was conducted at one of the public Senior High School in Tasikmalaya City on 2020/2021 academic year. The research method used is a quasi-experimental with a posttest only control group design. The research subject were 56 samples which were divided into two group, namely the experimental group and the control group. The sampling technique was carried out by purposive sampling. The instrument used in this study is a subjective rating scale with an assessment rubric of a scale of 1 – 8 including indicators of student responses about the material given by the teacher, student responses about prior knowledge, student responses about information components, and student responses in integrating information. The results show that learning using chunking techniques can help students process information better than conventional learning. The experimental group had a lower intrinsic cognitive load than the control group, so that the chunking technique can control students' intrinsic cognitive load.